椰子油的化学组成及功效研究进展Research progress on chemical composition and efficacy of coconut oil - 呙兴阳1,2，殷娇娇1,2，王澍3,4，黄何1,2，高盼1,2,3，潘保辉1,2，钟武1,2,3， 胡传荣1,2，何东平1,2,3，常超1,2 GUO Xingyang1,2, YIN Jiaojiao1,2, WANG Shu3,4, HUANG He1,2, GAO Pan1,2,3, PAN Baohui1,2, ZHONG Wu1,2,3, HU Chuanrong1,2, HE Dongping1,2,3, CHANG Chao1,2 (Zhongguo youzhi)
为更全面地了解椰子油的益处，推动对其功效的深入研究，综述了椰子油的化学组成及功效。椰子油是一种天然油脂，含有脂肪酸、酚类物质、脂溶性伴随物、挥发性物质等，可用于食品、日用化学品和医药等领域。丰富的化学成分赋予了椰子油诸多健康功效，如调节胆固醇水平和缓解心血管疾病、抗菌、抗病毒、抗炎、抗糖尿病、预防阿尔茨海默病、抗氧化等，其中近几年关于缓解心血管疾病和预防阿尔茨海默病的研究较为深入，但目前椰子油的开发利用尚不充分，未来可从食用药用和日用化学品两个方向进一步深入研究，推动其多元化开发。 In order to enhance understanding of the benefits of coconut oil and stimulate further research on its efficacy, the chemical composition and efficacy of coconut oil were summarized. Coconut oil is a natural oil that contains fatty acids, phenolic compounds, liposoluble components, volatile substances, etc, and it can be used in the food, daily-use chemicals, and pharmaceutical industries. These rich chemical composition contribute to various health benefits of coconut oil including cholesterol regulation, cardiovascular disease mitigation, antimicrobial, antiviral, anti-inflammatory, antidiabetes, prevention of Alzheimer′s disease, and antioxidant effects. Recent years more in-depth research on the cardiovascular diseases mitigation and prevention of Alzheimer′s disease have been witnessed. At present, the development and utilization of coconut oil is still insufficient, and in the future, further in-depth research can be carried out in the two directions of edible medicinal use and daily-use chemicals to promote its diversified development.